Impact of a Community-Based Pelvic Floor Kinesic Rehabilitation Program on the Quality of Life of Chilean Adult Women with Urinary Incontinence - Cifuentes-Silva, E; Cabello-Verrugio, C (Springer, 2023)
The pelvic floor forms the primary bottom tissue of the pelvic cavity. It comprises muscles that play a fundamental role in bowel and bladder emptying. Alterations of pelvic floor muscles will result in dysfunctions such as urinary incontinence (UI). Given the high prevalence of UI and its impact on the quality of life (QoL) in patients with pelvic floor muscle dysfunctions, it is necessary to implement public, community, and generalized programs focused on treating these dysfunctions. Objective: To determine the effect of a community rehabilitation program on QoL, UI severity, and pelvic floor muscle strength in patients with UI. Patients and Method: A descriptive prospective cohort study. Twenty subjects between 44 and 75 years old with a diagnosis of UI, participants of a community kinesic rehabilitation program on the pelvic floor in Maipú, Santiago, Chile, were evaluated. These volunteers were intervened for six months, and QoL was measured with the 36-Item Short-Form Health Survey (SF-36) and International Consultation on Incontinence Questionnaire Short-Form (ICIQ-SF) scales, UI severity with the Sandvick test, and pelvic floor muscle strength with the Oxford scale. Patients were followed up three months post-intervention. Results: Significant improvements were observed in all scales after applying for the community kinesic rehabilitation program, and the changes were maintained at a 3-month follow-up. Conclusions: Since the improvement in QoL, UI severity, and pelvic floor muscle strength after the intervention, it is relevant to consider the implementation of community programs aimed at education, screening, and early rehabilitation of these patients. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.